Visual Discourse in Postmodern Ceramics - Salman Kadhim, Rabab (Opción, 2019)
The present research deals with (optical discourse in postmodern ceramics). The concept of discourse represented an important axis in contemporary hu- man, cultural and cognitive studies. Art had its share in abundant aesthetic and nutrition studies, which it considers as a facet of cognitive and creative communication, both the sender and the recipient to understand, decode and reproduce his texts. Expressive self-oriented and always towards the other and the post-modern ceramics methods and techniques to highlight this dis- course, reinforced by a set of methods and creations ceramic. The present study is summarized in two chapters: Chapter I: the general framework and includes the problem of research and its importance and the goal of the re- search, which is summarized (reveal the semantics of optical discourse in post-modern ceramics). The limits of the research were limited to the study of ceramics done in America for the period (2000-2010). The second chapter: dealt with the first two (the concept of discourse), and the second (trends in the art of ceramics in post - modern arts). The third chapter contains the research procedures, including the research community, its sample, the research meth- od, the research tool, and the analysis of (5) contemporary American ceramic samples from the research community of (50) ceramic works. The descriptive approach - the method of analysis based on the indicators resulting from the theoretical framework as a tool for the analysis of the research sample. The fourth chapter contains the results of the research. 1. The semantics of the dis- course are linked to the individual potter’s emotional self, subconscious and psychological emotions within the framework of reading a number of prod- ucts. 2. The visual discourse in the ceramic text is manifested by the flexibility of the visual language and the multiplicity of meanings ie through the partici- pation of the recipient in the composition of the ceramic text. Conclusions 1. Postmodernism has contributed to the removal of the dis- course of traditional structures and replaced them with a discourse not related to the aesthetic phenomenon in order to reach the greatest possible unusual in dealing with art and ceramics in particular and regarded as a de- liberative value in the postmodern society. 2. The postmodernist discourse demonstrated a technical and stylistic diversity that paved the way for the diversity of ceramic currents in the United States of America to transform the political, economic and technological shifts of American society.